35 m Vertical Free Fall: How Impact Surface Influences Survival. (23rd October 2014) - Ehrnthaller, C.; Gebhard, F.
Abstract : We describe the accidental free fall of a 23-year-old construction worker, who fell 13 stories (approximately 35 meters) from a false work landing on a toilet container. On impact he broke through the roof of the container, which attenuated his fall and made his survival possible. The patient sustained a central spleen rupture, liver laceration, subdural hematoma, blunt thoracic trauma with a left-sided hematothorax and right-sided pneumothorax with serial bilateral rib fractures, and an unstable fracture of the 10th thoracic vertebra. Two thoracic drainages were inserted in the emergency department before the patient underwent emergency surgery for the management of his intra-abdominal injuries. On the third day after trauma the unstable fracture of the 10th thoracic vertebra was stabilized with an internal fixator. Following extubation on day 8 after trauma the patient did not show any peripheral neurological deficits but cerebral affection with a general slowdown. After only 21 days, the patient was discharged from the hospital to a rehabilitation center where work specific rehabilitation was started. Although the patient is not suffering from physical afflictions from the injury his daily life abilities are still limited due to cerebral damage.